Large-scale survey for novel genotypes of Plasmodium falciparum chloroquine-resistance gene pfcrt - Takahashi Nobuyuki; Tanabe Kazuyuki; Tsukahara Takahiro; Dzodzomenyo Mawuli; Dysoley Lek; Khamlome Boualam; Sattabongkot Jetsumon; Nakamura Masatoshi; Sakurai Miki; Kobayashi Jun; Kaneko Akira; Endo Hiroyoshi; et al. (Malaria Journal, 2012)
Abstract Background In Plasmodium falciparum , resistance to chloroquine (CQ) is conferred by a K to T mutation at amino acid position 76 (K76T) in the P. falciparum CQ transporter (PfCRT). To date, at least 15 pfcrt genotypes, which are represented by combinations of five amino acids at positions 72-76, have been described in field isolates from various endemic regions. To identify novel mutant pfcrt genotypes and to reveal the genetic relatedness of pfcrt genotypes, a large-scale survey over a wide geographic area was performed. Methods Sequences for exon 2 in pfcrt , including known polymorphic sites at amino acid positions 72, 74, 75 and 76, were obtained from 256 P. falciparum isolates collected from eight endemic countries in Asia (Bangladesh, Cambodia, Lao P.D.R., the Philippines and Thailand), Melanesia (Papua New Guinea and Vanuatu) and Africa (Ghana). A haplotype network was constructed based on six microsatellite markers located -29 kb to 24 kb from pfcrt in order to examine the genetic relatedness among mutant pfcrt genotypes. Results In addition to wild type (CVMNK at positions 72-76), four mutant pfcrt were identified; CVIET, CVIDT, SVMNT and CVMNT (mutated amino acids underlined). Haplotype network revealed that there were only three mutant pfcrt lineages, originating in Indochina, Philippines and Melanesia. Importantly, the Indochina lineage contained two mutant pfcrt genotypes, CVIET (n = 95) and CVIDT (n = 14), indicating that CVIDT shares a common origin with CVIET. Similarly, one major haplotype in the Melanesian lineage contained two pfcrt genotypes; SVMNT (n = 71) and CVMNT (n = 3). In Africa, all mutant pfcrt genotypes were the CVIET of the Indochina lineage, probably resulting from the intercontinental migration of CQ resistance from Southeast Asia. Conclusions The number of CQ-mutant lineages observed in this study was identical to that found in previous studies. This supports the hypothesis that the emergence of novel CQ resistance is rare. However, in the mutant pfcrt genotypes, amino ...